Overcoming immune resistance in ovarian cancer: checkpoint inhibitors, tumor microenvironment, and translational advances - Yue, Song; Wen, Tao; Liu, Xiaozhu; Tang, Juan; Liu, Yue; Peng, Shengxian (Frontiers in Oncology, 2026)
Ovarian cancer remains one of the most lethal gynecologic malignancies, with high recurrence rates and poor prognosis, particularly in platinum-resistant cases. Immune checkpoint inhibitors (ICIs), especially those targeting PD-1/PD-L1, have demonstrated success in multiple malignancies, yet their efficacy in ovarian cancer has been limited. Monotherapy with ICIs yields low response rates, prompting extensive investigations into combination strategies with chemotherapy, PARP inhibitors, and antiangiogenic agents. Some dual or triple regimens have shown promising activity, especially in biomarker-selected populations. However, immune resistance, immunosuppressive tumor microenvironment (TME), and biomarker heterogeneity remain significant barriers. This review summarizes the latest clinical progress in ICI-based therapies for ovarian cancer, evaluates current predictive biomarkers such as PD-L1 expression, TMB, and homologous recombination deficiency (HRD), and highlights the safety and toxicity profiles of immunotherapy. We also discuss the limitations of current clinical trials and the unmet need for precise immunotherapeutic strategies. Understanding the molecular and immunologic landscape of ovarian cancer is critical for identifying patients most likely to benefit from ICIs and guiding future clinical development.